Syngas production via CO2 reforming of CH4 over Ni-based SBA-15: Promotional effect of promoters (Ce, Mg, and Zr) - Chi, Cheng Chong; Lee, Peng Teh; Setiabudi, H. D. (Elsevier Ltd., 2019)
The promotional effect of different types of metals (Ce, Mg, and Zr) over Ni/SBA-15 which synthesized using ultrasonic co-impregnation technique were scientifically evaluated via CO2 reforming of CH4 (CRM). Characterizations including XRD, BET, FTIR, CO2-TPD were done to examine their physical attributes, metal-support interactions, and basicity properties. XRD results suggested that NiO particles were not distributed homogeneously within the confined framework of SBA-15 for Ni-Ce/SBA-15. Nevertheless, Mg and Zr promoters could effectively improve Ni dispersion over the SBA-15's siliceous framework and controlled the NiO crystallize sizes. The smallest NiO crystallite size of 9.3 nm was obtained by Ni-Zr/SBA-15. BET results verified the alteration of pore structure without changing the ordered structure of SBA-15 upon promoter addition. FTIR results suggested the partial transformation of Si–OH groups to the Si–O–X bond (X = Ce, Mg and Zr), whereas, CO2-TPD results confirmed the moderate basic sites present in Ni-Zr/SBA-15. H2-TPR evidenced the strongest metal-support interaction in Ni-Zr/SBA-15 owing to its high temperature reduction behaviour. At operating condition of P = 1.0 bar and WHSV = 15,000 mLg−1h−1, catalytic performance and stability ascended the trend of un-promoted < Ce-promoted < Mg-promoted < Zr-promoted Ni/SBA-15, in which Zr-promoted Ni/SBA-15 manifested the best catalytic activity (CO2 conversion = 93.8%; CH4 conversion = 88.3%; H2/CO ratio = 0.82). The ascendency catalytic activity and stability of Ni-Zr/SBA-15 catalyst were attributed to its favourable properties such as strong Si–O–Zr bond formation, smallest NiO crystallite size and a moderate amount of basic sites, which crucial for sintering restriction of NiO particles and carbon deposition, thus facilitated CRM reaction.